Orgasmic headache and middle cerebral artery dissection. Issue 5 (13th April 2006) - Szatmary, Z; Boukobza, M; Vahedi, K; Stapf, C; Houdart, E; Bousser, M G
Abstract : A patient with a 20 year history of primary orgasmic headache is described who, after suffering an unusually severe episode of orgasmic headache was found to have a middle cerebral artery dissection. This unusual association of primary and secondary orgasmic headache emphasises the need for a thorough diagnostic examination when the orgasmic headache differs from that of previous episodes or is associated with neurological symptoms.